2018
DOI: 10.30935/cet.414798
|View full text |Cite
|
Sign up to set email alerts
|

Publication Trends Over 10 Years of Computational Thinking Research

Abstract: The current study aimed to review studies on computational thinking (CT) indexed in Web of Science (WOS) and ERIC databases. A thorough search in electronic databases revealed 96 studies on computational thinking which were published between 2006 and 2016. Studies were exposed to a quantitative content analysis through using an article control form developed by the researchers. Studies were summarized under several themes including the research purpose, design, methodology, sampling characteristics, data analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 58 publications
(104 reference statements)
4
33
1
1
Order By: Relevance
“…All papers in the data set were published in 2013 or after. This lines up with previous research into computational thinking trends that showed that the number of studies around computational thinking started growing around the year 2013 [16]. This also aligns with the general trends of computational thinking literature broadly [16].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…All papers in the data set were published in 2013 or after. This lines up with previous research into computational thinking trends that showed that the number of studies around computational thinking started growing around the year 2013 [16]. This also aligns with the general trends of computational thinking literature broadly [16].…”
Section: Discussionsupporting
confidence: 87%
“…This lines up with previous research into computational thinking trends that showed that the number of studies around computational thinking started growing around the year 2013 [16]. This also aligns with the general trends of computational thinking literature broadly [16]. However, much of this study continues to be definitional, as well as research that presents ideas, rather than empirical [14,20].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Several articles published over the past several years have summarized and highlighted related development in CT research (e.g., Fennell et al 2020;Grover and Pea 2013;Ilic et al 2018;Kalelioglu et al 2016;Shute et al 2017;Tang et al 2020a). For example, Shute et al (2017) searched several databases (e.g., ERIC and PsycINFO) and selected, reviewed, and discussed 45 articles published since 2006 to come up with a working definition of CT, which emerged from their review primarily as a way of thinking and acting.…”
Section: A Brief Overview: Trends Of Ct Research and Instructionmentioning
confidence: 99%